1990
DOI: 10.1002/(sici)1097-4571(199006)41:4<264::aid-asi5>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy versus probabilistic models for user relevance judgments

Abstract: A crucial aspect of information retrieval is the process of making relevance judgments. Although this highly complex decision making procedure still eludes researchers, it is evident that a number of mental models are involved: models of the information need, retrieval system, database, user's knowledge in the subject area etc. In general, It is accepted that relevance judgments are made by evaluating documents for an overall conceptual match with the informatlon need. In this study, we take the view that, giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, a fuzzy approach may not always yield better results. Researchers in fields such as process control (Barrett and Woodall, 1997), health risk assessment (Kentel and Aral, 2005) and information retrieval (Koll and Srinivasan, 1990) have compared results using probability and possibility analysis, and found that some situations favour the former approach while other situations favour the latter. Hence, future research could first apply fuzzy theory to the uncertain parameters in the Taguchi quality loss framework, and then compare the suitability of the probability and possibility analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, a fuzzy approach may not always yield better results. Researchers in fields such as process control (Barrett and Woodall, 1997), health risk assessment (Kentel and Aral, 2005) and information retrieval (Koll and Srinivasan, 1990) have compared results using probability and possibility analysis, and found that some situations favour the former approach while other situations favour the latter. Hence, future research could first apply fuzzy theory to the uncertain parameters in the Taguchi quality loss framework, and then compare the suitability of the probability and possibility analysis.…”
Section: Discussionmentioning
confidence: 99%
“…New approaches to database structure such as multi-dimensional databases [13] and data warehousing [5] facilitate both storing vast quantities of data and using very complex queries to extract mformation. Fuzzy data management and retrieval enhance these efforts [22] [24].…”
Section: It For Gathering Intellectual Raw Materialsmentioning
confidence: 99%
“…New approaches to database structure such as multi-dimensional databases [13] and data warehousing [5] facilitate both storing vast quantities of data and using very complex queries to extract information. Fuzzy data management and retrieval enhance these efforts [19] [21].…”
Section: It For Gathering Intellectual Raw Materialsmentioning
confidence: 99%